Probing the role of Met221 in the unusual metallo-β-lactamase GOB-18 - Lisa, María Natalia (2012)
Metallo-beta-lactamases (MBLs) are the main mechanism of bacterial resistance against last generation b-lactam antibiotics such as carbapenems. Most MBLs display unusual structural features in their active sites, such as binuclear zinc centers without carboxylate bridging ligands and/or a Cys ligand in a catalytic zinc site. Cys221 is an essential residue for catalysis conserved in B1 and B2 lactamases, while most B3 enzymes present a Ser in this position. GOB lactamases stand as an exception within this picture, with a Met residue in position 221. Then, we obtained a series of GOB-18 point mutants in order to analyze the role of this unusual Met221 residue. We found that Met221 is essential for the protein stability, most likely due to its involvement in a hydrophobic core. In contrast to other known MBLs, residue 221 is not involved in metal binding or in catalysis in GOB enzymes, according to spectroscopic and kinetic studies. Our findings show that the essential catalytic features are maintained despite the structural heterogeneity among MβLs and suggest that a strategy to design general inhibitors should be undertaken on the basis of mechanistic rather than structural information.